The Medical Master Tutor Training - Constance Tucker; Kathy Gibbs (Association of American Medical Colleges, 2012)
Abstract Introduction Medical students are often challenged academically in the classroom. Peer tutoring is an excellent method to not only enhancing students' learning, but also increasing metacognition and self-regulation. This module provides a tutor training for medical students by presenting overview of theory so students learn how to instruct others on how they learn, as opposed to what they know. Methods The overall session takes approximately 2 hours to complete. During this time learners view a PowerPoint presentation for background information on learning theory and approaches to tutoring. Learners are then administered a tutor training assessment, which is discussed and feedback is provided. Results This session has been successfully incorporated into the curriculum offered to medical students at a college of medicine. Faculty evaluations demonstrate participant satisfaction and have improved the program over time. Student reactions to the program have been overwhelmingly positive. Students comment that they learned new information and felt more prepared to enter tutor sessions. At the university where the program was developed, students have reported less frustration with the quality of the tutors. Discussion Peer tutoring requires more than sharing knowledge. This resource provides medical students with the theoretical background they need to be effective peer tutors.